Salt stress and ambience in the culture of yellow passion-fruit - da Conceição Mendes Semedo, Tamires; Gomes de Sousa, Geocleber; Castelo Sousa, Henderson; Baldé, Bubacar; Nojosa Lessa, Carla Ingryd; Machado de Sousa, José Thomas (Revista Brasileira de Engenharia de Biossistemas, 2022)
Salt stress negatively affects the emergence and initial growth of crops. However, the use of protected environments emerges as an alternative to enhance these parameters. In this sense, the objective was to evaluate the effect of different environments and the salinity of the irrigation water on the emergence and development of yellow passion-fruit seedlings. The experiment was conducted at the University for International Integration of the Afro-Brazilian Lusophony, in the city of Redenção, Ceará. The experimental design was entirely randomized in a subdivided plot scheme, with four cultivation environments under different shading screens (black screen; white screen; red screen; all with 50% shading; and full sun), and two electrical conductivities of irrigation water: 0.3 dS m-1 and 3.0 dS m-1, with five repetitions of 25 seeds. The protected environment with 50% black roofing stood out from the others providing a better percentage of emergence, seedling height, stem diameter, number of leaves and radicle length in yellow passion-fruit. The deleterious effects of salts on the rate of emergence and shoot dry matter were reduced when the 50% black shade cloth was used. Irrigation with water of higher conductivity caused reductions and retardation in the emergence of passion-fruit. Besides negatively affecting seedling height, stem diameter and shoot dry matter.